The representation of women in video games: a comparative analysis between Tomb Raider and the Horizon saga - Francesco Barbalace; Aida Picone (Culture e Studi del Sociale)
This article examines the representation of female protagonists in video games by conducting a comparative analysis of Lara Croft from the Tomb Raider series and Aloy from Horizon series. The study investigates the evolutionary changes in the portrayal of these characters and their relationship with contemporary social imaginaries and sensitivities. The article adopts a theoretical framework that combines perspectives from social imaginaries and media studies. The research methodology involves analyzing the narrative storytelling, body representations, and costume design of the characters. The findings highlight the transformations in the depiction of Lara Croft over time, from a hypersexualized damsel in distress to a more complex and empowered character. In the case of Aloy, her representation challenges traditional beauty standards and incorporates imperfections, reflecting an evolving societal acceptance. The study emphasizes the reciprocal influence between societal changes and representations in video games, highlighting the role of these media in shaping collective imaginations.